OPTIMALISASI PERSIAPAN KONSELING KELOMPOK BERBASIS ANALISIS TRANSAKSIONAL: PANDUAN PRAKTIS - Nasution, Salsabila; S, Neviyarni; Netrawati; Hariko, Rezki (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2024)
Group counseling is one of the important approaches in Guidance and Counseling (BK) at school, which aims to help students overcome emotional, social, and academic problems. One of the relevant approaches to be applied in group counseling is Transactional Analysis (AT), which focuses on understanding communication patterns between individuals. Despite the great potential of AT in improving the effectiveness of group counseling, many counseling teachers still face challenges in its application. This study aims to identify the problems faced by counseling teachers in implementing AT-based group counseling and provide practical guidance to optimize its implementation. Through a qualitative approach with a case study, data were collected through interviews with three counseling teachers in Medan City. The results showed that the implementation of AT-based group counseling was not optimal, with most teachers tending to use the general guidance approach. The main problem found was the lack of understanding about AT theory, particularly about the concepts of Ego States (Parent, Adult, Child) and techniques such as Reframing and Strokes. Therefore, this study suggests the importance of increasing basic understanding of AT, careful preparation before group counseling, and practical training for counseling teachers so that they can manage group dynamics more effectively. With optimal implementation, AT-based group counseling is expected to have a positive impact on students' emotional, social, and academic development.